2018
DOI: 10.1037/pspa0000123
|View full text |Cite
|
Sign up to set email alerts
|

Towards a deeper understanding of impression formation—New insights gained from a cognitive-ecological perspective.

Abstract: Impression formation is a basic module of fundamental research in social cognition, with broad implications for applied research on interpersonal relations, social attitudes, employee selection, and person judgments in legal and political context. Drawing on a pool of 28 predominantly positive traits used in Solomon Asch's (1946) seminal impression studies, two research teams have investigated the impact of the number of person traits sampled randomly from the pool on the evaluative impression of the target pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 54 publications
7
55
0
Order By: Relevance
“…The novel manipulation of granting the power of seeing more or fewer samples to participants enabled us to identify the underlying mechanism. Consistent with past Running head: FACE STEREOTYPES FROM INSUFFICIENT STATISTICAL LEARNING work (e.g., Klein and O'Brien, 2018;Prager, Krueger, & Fiedler, 2018), we found that participant-generated samples are much smaller than the samples needed to gain an accurate picture of the data. As a result, such insufficient sampling makes spurious beliefs sticky, and resistant to updating even when faced with the complete environmental data.…”
Section: Running Head: Face Stereotypes From Insufficient Statistical Learningsupporting
confidence: 87%
See 1 more Smart Citation
“…The novel manipulation of granting the power of seeing more or fewer samples to participants enabled us to identify the underlying mechanism. Consistent with past Running head: FACE STEREOTYPES FROM INSUFFICIENT STATISTICAL LEARNING work (e.g., Klein and O'Brien, 2018;Prager, Krueger, & Fiedler, 2018), we found that participant-generated samples are much smaller than the samples needed to gain an accurate picture of the data. As a result, such insufficient sampling makes spurious beliefs sticky, and resistant to updating even when faced with the complete environmental data.…”
Section: Running Head: Face Stereotypes From Insufficient Statistical Learningsupporting
confidence: 87%
“…Similarly, when judging a person's intellect or character, people thought they would choose to view five pieces of information, but only chose to view three pieces. Likewise, recent impression formation research has shown that participantdetermined samples are substantially smaller than experimenter-determined samples (Prager, Krueger, & Fiedler, 2018). When forming impressions, if the first few traits happened to convey a clear-cut impression (e.g., Bob is friendly, nice, trustworthy, and helpful), then people cut the sample short.…”
Section: Running Head: Face Stereotypes From Insufficient Statistical Learningmentioning
confidence: 99%
“…Almost ideal MC conditions are implemented in so-called sampling approaches to judgment and decision research ( Fiedler & Kutzner, 2015 ). Because the results of information search and environmental sampling processes are assessed independently of the final judgment and decision phenomena to be explained, the experimental task renders the hypothesized IV (i.e., sampling error and bias) amenable to direct empirical assessment, independently of the DVs measuring judgments and decisions ( Denrell & Le Mens, 2012 ; Prager et al, 2018 ). It may be no coincidence that sampling theories are so illuminating and satisfactory and that the resulting empirical findings are so robust.…”
Section: Immediate and Mediate Implicationsmentioning
confidence: 99%
“…Much progress has been made in theory development and theory testing, although it is not always clear what is meant by "theory." Rigorous hypothetico-deductive processes are not the rule in experimental design (Prager et al, 2018), and many researchers settle for vague verbal descriptions of phenomena (Gigerenzer, 1998(Gigerenzer, , 2010.…”
Section: History Inspires Research Which Helps To Explain Historymentioning
confidence: 99%